Extremely loud mating songs at close range in white bellbirds - Podos, Jeffrey (Current Biology, 2020)
Holzner et al. show that macaques provide a net benefit to oil palm harvest by reducing losses due to rodent pests on oil palm plantations. © 2019 Elsevier LtdSexual selection in many animal species favors the evolution of elaborate courtship traits. Such traits might help signalers convey, and receivers discern, information about signaler quality; or they might be favored by perceptual or aesthetic preferences for elaborateness or beauty [1–3]. Under either scenario we expect sexual trait elaboration to be countered by proximate constraints rooted in animals’ morphology, physiology and phylogenetic history [3,4]. During expeditions to a montane rainforest in the Brazilian Amazon, we obtained amplitude-calibrated measures of mating songs in two species of cotingas, the white bellbird (Procnias albus) and the screaming piha (Lipaugus vociferans). The screaming piha sings the loudest songs of any passerine bird previously documented [5]. However, we find that white bellbirds are >9 dB louder, and thus achieve roughly triple the sound pressure levels of pihas. Mechanical constraints on amplitude, and thus limits on the reach of sexual selection, are revealed by trade-offs between maximal sound pressure and song duration. We find that song amplitude in bellbirds is context-dependent: when a female was on the display perch, a male bellbird sang only his louder song type, swiveling his body mid-song to face the female head on. We know of no other species in which such high-amplitude vocal signals are directed to receivers in such close proximity. We propose that bellbird females balance an interest in sampling males at close range with a need to protect themselves from hearing damage. © 2019 Elsevier Ltd